The complete chloroplast genome of a medicinal plant Anemone flaccida (Ranunculaceae). Issue 3 (2nd July 2020) - Tang, Yuwen; Liu, Yifei; Liu, Man; Hu, Zhigang; Huang, Bisheng
Abstract: Anemone flaccida has long-term been used in Chinese traditional medicine with the effects of anticancer, anti-inflammatory, antimicrobial properties, and immune regulation. However, the genomic information of this species is limited, which hinders its further medicinal application. In the present study, the complete chloroplast genome of A. flaccida was sequenced and assembled. The genome size was 157, 614 bp in length, consisting of a pair of inverted repeat regions (IR, 31, 184 bp), a large single copy (LSC, 79, 055 bp), and a small single copy (SSC, 16, 191 bp). A total of 138 genes were annotated, including 90 protein-coding genes, 40 tRNA genes, and eight rRNA genes. The GC content of the genome was 37.74%. A phylogenetic analysis on the basis of the whole chloroplast genome sequences further suggested a close relationship between A. flaccida, A. narcissiflora, and A. trullifolia . Collectively, the A. flaccida chloroplast genome provided new genomic resources which will improve its research and application in the future.